2018
DOI: 10.1097/hrp.0000000000000158
|View full text |Cite
|
Sign up to set email alerts
|

Living High and Feeling Low: Altitude, Suicide, and Depression

Abstract: After participating in this activity, learners should be better able to:• Assess epidemiologic evidence that increased altitude of residence is linked to increased risk of depression and suicide• Evaluate strategies to address hypoxia-related depression and suicidal ideation ABSTRACT: Suicide and major depressive disorder (MDD) are complex conditions that almost certainly arise from the influences of many interrelated factors. There are significant regional variations in the rates of MDD and suicide in the Uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
50
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 66 publications
(53 citation statements)
references
References 134 publications
3
50
0
Order By: Relevance
“…AGBL2 is an ATP/GTP binding protein implicated in brain structure and function [ 33 ]. SUCLA2 is a mitochondrial tricarboxylic acid cycle protein recently implicated in energy supply to the synapse [ 34 ], and is possibly associated with recent findings linking suicide risk and hypoxia [ 35 ]. APH1B is a transmembrane protein associated with risk of Alzheimer’s [ 36 ] and Parkinson’s [ 37 ] diseases.…”
Section: Discussionmentioning
confidence: 99%
“…AGBL2 is an ATP/GTP binding protein implicated in brain structure and function [ 33 ]. SUCLA2 is a mitochondrial tricarboxylic acid cycle protein recently implicated in energy supply to the synapse [ 34 ], and is possibly associated with recent findings linking suicide risk and hypoxia [ 35 ]. APH1B is a transmembrane protein associated with risk of Alzheimer’s [ 36 ] and Parkinson’s [ 37 ] diseases.…”
Section: Discussionmentioning
confidence: 99%
“…From a biophysiological and psychological perspective, increased suicide rates could be attributed to depression and/or mood instability, related to high-altitude hypoxia [ 33 , 34 , 35 ]. However, systematic physiological responses to ambient oxygen levels are extremely complicated and more research is needed to establish a robust causal link between altitude, hypoxia, mood disorder and suicide risk [ 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although our findings do not show that higher altitude contributes causally to suicide risk among veterans, they invite speculation about mechanisms that might connect altitude and suicide. Although the slight decrease in arterial oxygen concentration associated with living chronically at moderate elevation has not been shown to have clinical effects, it has been suggested that residing at higher altitudes may result in chronic relative hypoxia, which could in turn impact brain processes such as monoamine synthesis and bioenergetics (Brenner et al, 2011b; Fiedler et al, 2012; Kim et al, 2014b; Kious et al, 2018).…”
Section: Discussionmentioning
confidence: 99%